Light Scattering, CD, and Ligand Binding Studies of Ferrihemoglobin-Polyelectrolyte Complexes - Xia, J.; Dubin, P.L.; Kokufuta, E.; Havel, H.; Muhoberac, B.B.
Quasi-elastic light scattering (QELS), electrophoretic light scattering (ELS), CD spectroscopy, and azide binding titrations were used to study the complexation at pH 6.8 between ferrihemoglobin and three polyelectrolytes that varied in charge density and sign. Both QELS and ELS show that the structure of the soluble complex formed between ferrihemoglobin and poly(diallyldimethylammonium chloride)[PDADMAC]varies with protein concentration. At fixed 1.0 mg/mL polyelectrolyte concentration, protein addition increases complex size and decreases complex mobility in a tightly correlated manner. At 1.0 mg/mL or greater protein concentration, a stable complex is formed between one polyelectrolyte chain and many protein molecules (i.e., an intrapolymer complex)with apparent diameter approximately 2.5 times that of the protein-free polyelectrolyte. Under conditions of excess polyelectrolyte, each of the three ferrihemoglobin-polyelectrolyte solutions exhibits a single diffusion mode in QELS, which indicates that all protein molecules are complexed. CD spectra suggest little or no structural disruption of ferrihemoglobin upon complexation. Azide binding to the ferrihemoglobin-poly(2-acrylamide-2-methylpropanesulfonate)[PAMPS]complex is substantially altered relative to the polyelectrolyte-free protein, but minimal change is induced by complexation with an AMPS-based copolymer of reduced linear charge density. The change in azide binding induced by PDADMAC is intermediate between that of PAMPS and its copolymer
Keywords: HEMOGLOBIN-POLYELECTROLYTE COMPLEXES; PROTEIN-POLYELECTROLYTE COMPLEXES; LIGHT SCATTERING; CD; LIGAND BINDING